Capturing the benefits that emerge from regional sustainability networks: The Castile–La Mancha network of sustainable cities and towns1. (10th April 2014) - Echebarria, Carmen; Barrutia, Jose M.; Aguado, Itziar; Apaolaza, Vanessa; Hartmann, Patrick
Abstract: A great deal of regional research has focused on the innovation‐competitiveness‐growth chain, which is implicit in territorial innovation models (TIMs). TIMs literature has neglected or subordinated social and ecological regional conditions. This research adopts a broader perspective by: ( i ) studying an interscalar intergovernmental network aimed at meeting tridimensional sustainable development (SD) goals; and ( ii ) showing why this arrangement is successful. The network members are the regional government and provincial councils, which act as network promoters, and the municipalities. We model the network as a platform for integrating both pre‐existing idiosyncratic resources and emergent resources/benefits that come from rich and regular interactions (in the shape of learning, enjoyment, reputation, identification, and attitude towards citizen participation); resources integration leads to network member satisfaction. This view is supported by data concerning a network in a Spanish autonomous community (region), Castile–La Mancha. We see this study as a first step towards more systematic research on what might be termed 'territorial sustainability models'.